Migraine and Obesity: Is There a Relationship? A Systematic Review and Meta-Analysis of Observational Studies - Hatami, Mahsa; Soveid, Neda; Lesani, Azadeh; Djafarian, Kurosh; Shab-Bidar, Sakineh (CNS & Neurological Disorders - Drug Targets, 2021)
Background and Objective: Many studies have evaluated the risk of migraine headache in obese persons, suggesting controversial conclusions. The aim of this systematic review and meta- analysis of the observational studies was to clarify the association between migraine and obesity. Methods: Scopus and PubMed electronic databases were systematically searched up to February 2019 for observational studies providing data dealing with migraine disorder in obese subjects, as well as normal-weight controls. The random effects model was applied for assessing pool effect size, and inter-study heterogeneity was evaluated by conducting subgroup analyses. Results: Among 1122 publications, 16 studies (10 cross-sectional, 5 cohort studies and 1 case-control study) were detected and were included in the meta-analysis. The pooled data analysis illustrated an elevated risk of migraine headache (Prevalence ratio estimate = 1.29, 95% CI, 1.15 - 1.44, p = 0.000) in obese individuals compared to normal-weight persons. Subgroup analyses revealed that geographical distribution was an important source of heterogeneity (p = 0.04). Significantly greater migraine prevalence was found in European and Asian patients, but no statistically significant relationship with obesity was observed in American patients. Conclusion: Based on a cumulative meta-analysis of available studies indicating an association between migraine and obesity, obesity can be appropriately considered as an overall risk factor for migraine headaches. Additional high-quality original studies considering frequency, severity, and duration of headaches are required to clarify confident evidence.
Keywords: dyslipidemia